Autosomal dominant polycystic kidney disease (ADPKD) with multiple complications: Management challenges - Djajapranata, Kenneth M.; Tjempakasari, Artaria (Narra Sains Indonesia, 2024)
Autosomal dominant polycystic kidney disease (ADPKD) is the most common hereditary polycystic kidney disease characterized by renal enlargement, resulting in renal failure. In Indonesia, the exact prevalence of ADPKD is unknown due to limited reports on the disease. The aim of this study was to report a case of a patient with ADPKD with multiple complications. A 54-year-old male presented to the emergency room of Dr. Soetomo Academic General Hospital, Surabaya, Indonesia, with a chief complaint of dark-red-colored urine for one week. There was a progressive abdominal enlargement over the past five years, which had become more tense and rigid for the past one month. The patient had a history of fatigue and hypertension with routine follow-up. Physical examination on admission showed normal vital signs, and the abdominal assessment revealed a palpable hard mass approximately 4 cm in size in the right upper abdomen. Laboratory test indicated anemia, leukocytosis, lymphopenia, proteinuria, hematuria, leukocyturia, and elevated serum creatinine and urea levels. Abdominal imaging using ultrasonography, computed tomography (CT) scan, and magnetic resonance imaging (MRI) revealed bilateral kidney and liver enlargement containing multiple cysts, suggesting polycystic kidney and liver disease. There was a ruptured cyst in the middle of the left kidney pole with minimal ascites found in the CT scan. The MRI exhibited the presence of multiple cysts in both kidneys, partially filled with blood. The patient was diagnosed with ADPKD, gross hematuria, acute or chronic kidney disease (CKD), urinary tract infection (UTI), normochromic-normocytic anemia, and metabolic acidosis. Dietary control with high-calorie, high-protein, and low-salt diet; fluid balance; and other symptomatic medications were initiated. It is critical to be aware of risk factors associated with the rapid progression of ADPKD in order to be able to provide a favorable impact on the disease prevention and management.